Sustainability and scalability of egg consumption in Burkina Faso for infant and young child feeding - Moore, Emily V.; Wood, Elizabeth; Stark, Heather; Wereme N'Diaye, Aissata; McKune, Sarah L. (Frontiers in Nutrition, 2023)
Malnutrition is a significant challenge to the health of women and children in Burkina Faso. Given the critical role of animal source food on the health of infants and young children (IYC), interventions continue to explore the potential for eggs to prevent malnutrition. Using data from the Un Oeuf intervention, which significantly increased IYC egg consumption, combined with quantitative and qualitative data from endline and three-month follow-up, we explore the barriers and facilitating factors to IYC egg consumption and the sustainability and scalability of the intervention. Child egg consumption was high at follow-up in the Control, Partial, and Full Intervention arms (83.3%, 88.2%, and 100, respectively). The Full Intervention arm had the highest mean number of eggs consumed (2.9, 2.6, and 5.7), which reflected a slight reduction from endline (6.2). All participants owned chickens at follow-up (100%), however, flock size varied. The Full Intervention arm had more chickens (mean 8.8) than the Control (5.1) or Partial Intervention (6.2) arms, which was a 50% reduction in below endline (18.5 chickens). Qualitative results indicate that chicken ownership, education about the nutritional value of eggs, and spousal support facilitated IYC egg consumption. Barriers included egg production, cultural taboos, and animal health. Motivational factors reported included the observed improvement in child health, increased availability of mothers’ time, and mothers’ financial independence. Knowledge sharing within the Full and Partial Intervention groups was widely reported, and the sustainability of IYC egg consumption was reinforced by accountability among mothers and to community leaders, flipbooks distributed during the project, and high motivation. Main findings indicate that mothers who received the full Un Oeuf intervention were able to overcome barriers to feeding their child an egg daily, were able to improve their livelihood, were motivated to continue feeding their child eggs, and saw the addition of eggs into the child’s diet as sustainable. Future nutrition sensitive agriculture interventions should consider tailoring this approach for other LMIC contexts. Future research is needed to explore a possible threshold in the number of household chickens necessary to continuously feed a child an egg a day.